1987
DOI: 10.1177/002383098703000403
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Speech Rhythm and Pitch to Speaker Recognition

Abstract: Using a Fourcin laryngograph, Lx recordings of three male speakers were made. After manipulation, the Lx signals were presented to a group of eight listeners, who performed both an AX discrimination and a speaker identification test. The results show that the listeners made use of the three parameters varied in the listening tests, viz. speech rhythm, F0 contour and F0 height. Furthermore, the data suggest that the relevance of these different parameters for speaker recognition is speaker-dependent rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
3
22
1
1
Order By: Relevance
“…There were also significant negative correlations between correct Twin B identification scores and Twin B's corresponding FO onset, FO SD, and FO range values (see Table 3). Perhaps fundamental frequency may have played some role in this speaker-identification task, a suggestion that is supported by previous studes which have also reported on the contribution of FO to speaker-identification (Abberton & Fourcin, 1978;Van Dommelen, 1987, 1990. These results suggest that identifications of the hvins from the pure syllables were higher with lower FO parameter values.…”
Section: Discussionsupporting
confidence: 80%
“…There were also significant negative correlations between correct Twin B identification scores and Twin B's corresponding FO onset, FO SD, and FO range values (see Table 3). Perhaps fundamental frequency may have played some role in this speaker-identification task, a suggestion that is supported by previous studes which have also reported on the contribution of FO to speaker-identification (Abberton & Fourcin, 1978;Van Dommelen, 1987, 1990. These results suggest that identifications of the hvins from the pure syllables were higher with lower FO parameter values.…”
Section: Discussionsupporting
confidence: 80%
“…From a speech production perspective, a speaker’s fundamental frequency relates to the rate of vocal fold vibration (known as glottal pulse rate), and formant spacing is affected by the length and shape of the vocal tract—which are relatively fixed for a speaker, although can be modified slightly by changing the positions of the articulators, such as the tongue and lips. Previous research demonstrates that listeners use both fundamental frequency and speech formants to judge the identity of people who are familiar ( LaRiviere, 1975 ; Abberton and Fourcin, 1978 ; Van Dommelen, 1987 , Van Dommelen, 1990 ; Lavner et al., 2000 ; Lavner et al., 2001 ; Holmes et al., 2018a ) and unfamiliar ( Matsumoto et al., 1973 ; Walden et al., 1978 ; Murry and Singh, 1980 ; Baumann and Belin, 2009 ; Gaudrain et al., 2009 ). To extend the current model to recognise voices, the next step is to specify how combinations of fundamental and formant frequencies are used to infer speaker identity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that spectral information of vocalizations can be used for identification by nonhuman primates (Rendall et al., ; Weiss et al., ), and our study showed that fine variations in pitch of the order of semitones can be distinguished and represented by A1 neurons. It has also been reported that voice pitch can be used for speaker identification in humans (Dommelen, ; Gelfer & Mikos, ; Walker, Bizley, King, & Schnupp, ), and for individual identification in other nonhuman primates (Zoloth et al., ; Kojima et al., ) and birds (Nelson, ). The current study provides a foundation for future work studying the neural circuits involved voice discrimination in awake behaving animals, which will undoubtedly include other areas in addition to A1.…”
Section: Discussionmentioning
confidence: 99%